KESALAHAN FONOLOGI, MORFOLOGI, SINTAKSIS PADA FILM “AYAH, INI ARAHNYA KE MANA, YA?” KARYA KUNTZ AGUS - Ridho Sastro Panjaitan; Tabita Tesalonika Simaremare; Mutiara Aprilia; Mannawa Salwa; Muharinna Harahap (STKIP Subang, 2026)
This study aims to explore language errors in phonology, morphology, and syntax in the film